Bahasa Inggris - Cipta canggih Perdana; Sinar Dharmayana Putra; Yuyun Karystin Meilisa Suade; Monalisa Monalisa (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study examines when and how viral marketing and social proof shape purchase intention in social commerce, and whether Fear of Missing Out (FOMO) mediates these effects. Drawing on Social Influence Theory, we model viral marketing and social proof as antecedents, FOMO as a mediator, and purchase intention as the outcome. Data were collected from 231 active social commerce users in Indonesia and analyzed using variance-based structural equation modeling (PLS-SEM). The measurement model met accepted criteria for reliability and convergent validity. The structural results show that viral marketing exerts a positive and significant direct effect on purchase intention while also increasing FOMO. Social proof significantly elevates FOMO but does not directly influence purchase intention, indicating that endorsement cues operate primarily through affective urgency rather than as stand-alone drivers. FOMO has a positive and significant effect on purchase intention and mediates the paths from both viral marketing and social proof to purchase intention, implying partial mediation for viral marketing and full mediation for social proof. These findings advance theory by integrating normative and informational influence with an affective mechanism central to the attention economy. Managerially, they suggest prioritizing diffusion design and credible validation cues that ethically heighten urgency, while monitoring authenticity and overload to prevent reactance.